Fabrication of humidity sensor using ta-doped TiO₂ nanoflower and ta-doped TiO₂ nanoflower / RGO nanocomposite / Musa Mohamed Zahidi - Mohamed Zahidi, Musa (2023)
In this work, the feasibility of using nanostructured titanium dioxide (TiO2) film as a sensing element of a resistive-type humidity sensor was explored. Flower-like TiO2 nanostructure have been successfully prepared on glass substrate using a combination of radio frequency (RF) magnetron sputtering and modified solution immersion methods, eliminating the need for fluorine-doped tin oxide (FTO) substrate and autoclave. The TiO2 seed layer was deposited on a glass substrate using RF magnetron sputtering to replace the FTO substrate for TiO2 nanostructures growth. The properties of the prepared flower-like TiO2 nanostructure films were characterised using field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDS), high-resolution transmission electron microscopy (HR-TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction spectroscopy (XRD), Raman spectroscopy, reverse double beam photoacoustic spectroscopy (RBD-PAS), Hall-effect measurement, contact angle measurement, and humidity sensor response measurement. Humidity sensor fabricated using this flower-like TiO2 nanostructure has showed excellent sensor response due to the immense surface area provided by the unique structure. The effect of Tantalum (Ta) doping on the characteristics of TiO2 nanoflower was also examined. Evolution of TiO2 structure from nanoflower to microsphere was observed with the addition of Ta, leading to the improvement of humidity sensor response. The optimum Ta doping concentration is at 3.0 at.% which yielded humidity sensor response of 53,909%. Reduced graphene oxide (rGO) has also been added to the TiO2 nanoflowers to produce nanocomposite with enhanced humidity sensing performance. A solution containing rGO was prepared and drop-casted onto TiO2 nanoflowers. The nanocomposite recorded maximum sensor response of 39,590%. Finally, to assess the combined effect of Ta-doping and rGO addition, Ta-doped TiO2 microsphere/rGO nanocomposite have been prepared. The humidity sensor fabricated using the material exhibited maximum humidity sensor response of 232,152%. In summary, the improved humidity sensor performance can be attributed to enhanced surface area, increased oxygen vacancy sites, reduced electrical resistivity, and formation of Schottky junction. The findings from this study suggest that this type of material has the potential to be employed to fabricate high sensitivity humidity sensing device.